2023
DOI: 10.35869/vial.v0i20.4354
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative writing and patterns of interaction in young learners: The interplay between pair dynamics and pairing method in LRE production

Abstract: A considerable body of research within the Socio-cultural theory (Lantolf & Appel, 1994) examines how learners express their linguistic gaps verbally, or question their own or others’ language use when writing collaboratively, i.e., produce Languagerelated episodes (LREs; Swain & Lapkin, 1998). Several studies have also explored the effect that different patterns of interaction (Storch, 2002) have on the production of LREs with adult learners (e.g., Mozaffari, 2017; Storch & Aldosari 2013), but lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…These results were replicated in a later study (Storch & Aldosari, 2012), which demonstrated that LP learners took fewer and shorter turns when interacting with HP learners, compared with when they were paired with other LP peers, because of the tendency toward unequal relationships (expert/novice or dominant/passive). Basterrechea and Gallardo‐del‐Puerto (2023) also attested that the correct resolution of LRES was much higher in collaborative or expert/novice pairs. Other studies noted that learners collaborated more equally with peers who shared the same proficiency levels but were more likely to play a less active role with more proficient peers (e.g., Kim & McDonough, 2008; Kowal & Swain, 1994; Watanabe & Swain, 2007).…”
Section: Peer Interaction and Language‐related Episodesmentioning
confidence: 89%
“…These results were replicated in a later study (Storch & Aldosari, 2012), which demonstrated that LP learners took fewer and shorter turns when interacting with HP learners, compared with when they were paired with other LP peers, because of the tendency toward unequal relationships (expert/novice or dominant/passive). Basterrechea and Gallardo‐del‐Puerto (2023) also attested that the correct resolution of LRES was much higher in collaborative or expert/novice pairs. Other studies noted that learners collaborated more equally with peers who shared the same proficiency levels but were more likely to play a less active role with more proficient peers (e.g., Kim & McDonough, 2008; Kowal & Swain, 1994; Watanabe & Swain, 2007).…”
Section: Peer Interaction and Language‐related Episodesmentioning
confidence: 89%